Diesel's Devious Deed and Other Thomas the Tank Engine Stories. - Awdry, Rev. W. (New York, NY : Random House, 1992)
Diesel causes no end of trouble among the engines when he arrives at Thomas the Tank Engine's train yard.
Keywords: Railroads - Trains - Fiction; Behavior - Fiction; Mitton, David, ill; Permane, Terry, ill; Awdry, W. Railway Series; Thomas the Tank Engine and Friends